2017
DOI: 10.1017/s1355617717000649
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Investigations of Human Amnesia: Insights Into the Role of the Medial Temporal Lobes in Cognition

Abstract: The past 30 years of research on human amnesia has yielded important changes in our understanding of the role of the medial temporal lobes (MTL) in memory. On the one hand, this body of evidence has highlighted that not all types of memory are impaired in patients with MTL lesions. On the other hand, this research has made apparent that the role of the MTL extends beyond the domain of long-term memory, to include working memory, perception, and future thinking. In this article, we review the discoveries and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…Any further autobiographical episodes retrieved are categorised as 'external', and Strikwerda-Brown, Mothakunne, have now attempted to separate out the sub-components of external content. I am happy to concur with the statement by Verfaellie and Keane (2017) that "the potential impact of different approaches to testing and scoring autobiographical memory also has garnered recent attention and remains an area of active investigation." has postulated two types of provoked confabulation; and Schnider (2017) distinguished between four types of confabulation, a central notion being that spontaneous confabulation is defined by a patient acting upon his/her erroneous memories.…”
Section: Types Of Confabulationmentioning
confidence: 57%
See 1 more Smart Citation
“…Any further autobiographical episodes retrieved are categorised as 'external', and Strikwerda-Brown, Mothakunne, have now attempted to separate out the sub-components of external content. I am happy to concur with the statement by Verfaellie and Keane (2017) that "the potential impact of different approaches to testing and scoring autobiographical memory also has garnered recent attention and remains an area of active investigation." has postulated two types of provoked confabulation; and Schnider (2017) distinguished between four types of confabulation, a central notion being that spontaneous confabulation is defined by a patient acting upon his/her erroneous memories.…”
Section: Types Of Confabulationmentioning
confidence: 57%
“…In a recent review, Sekeres, Winocur, and Moscovitch (2018) concluded the same, but postulated specialisation in subfields along the long axis of the hippocampi. Many recent studies indicate widespread cortical activations during autobiographical memory retrieval (Svoboda, McKinnon, & Levine, 2006) or postulate important interactions between cortical and medial temporal regions in autobiographical retrieval (Bonnici & Maguire, 2018;Ghosh, Moscovitch, Colella, & Gilboa, 2014;Irish et al 2018;McCormick, St-Laurent, Ty, Valiante, & McAndrews, 2015;McCormick, Ciaramelli, De Luca, & Maguire, 2018;Moscovitch, Cabeza, Winocur, & Nadel, 2016;Simons & Spiers, 2003;Verfaellie & Keane, 2017).…”
Section: Theories Of Ra and The Temporal Gradientmentioning
confidence: 99%
“…Through these analogies, our model challenged the traditional view of the hippocampus only ascribed to the explicit/adaptive memory by an innate/implicit memory structure and essential mediator to explicit (declarative) memory. Although the hippocampus and adjacent structures of the medial temporal lobe (MTL) share function homology to the mushroom bodies of invertebrates (such as insects and crustacea) ( 24 26 ) and are evolutionarily ancient brain regions, the involvement of MTL in short-term associative memory is recent ( 27 , 28 ). Hence, MTL bridges both implicit and explicit processes, which is not a new idea, but in line with kinetic models ( 29 ), functional neuroimaging studies ( 30 , 31 ), and processing-based models ( 32 ).…”
Section: A Journey From Consciousness To Cell Biologymentioning
confidence: 99%
“…We recall our past experiences in the form of autobiographical memories, and are also able to imagine potential future events. Along with spatial navigation ( O’Keefe and Nadel, 1978 ; Maguire et al, 2000 ; Ekstrom et al, 2003 ; Moser et al, 2008 ), these cognitive functions have been linked with a brain structure called the hippocampus ( Scoville and Milner, 1957 ; Tulving, 1985 ; Klein et al, 2002 ; Svoboda et al, 2006 ; Addis et al, 2007 ; Verfaellie and Keane, 2017 ). Views differ on the precise role played by the hippocampus in supporting these seemingly disparate cognitive functions (e.g., Schacter et al, 2012 ; Maguire and Mullally, 2013 ; Moscovitch et al, 2016 ; Ekstrom and Ranganath, 2018 ).…”
Section: Introductionmentioning
confidence: 99%